HAK DAN KEWAJIBAN SUAMI ISTERI DALAM ISLAM DAN HUKUM PERKAWINAN DI INDONESIA - Misbachul Fitri, Abdul Basit (USRATUNA: Jurnal Hukum Keluarga Islam, 2019)
Islamic law and marriage law are at the same level as rules and laws that must be obeyed by adherents of religion and contain benefits for the ummah. Marriage is a religious order that has the value of worship that produces rewards, when religious orders are carried out it will produce happiness and benefit for the worshipers. The existence of rights and obligations of husband and wife in Islam and marriage law in Indonesia is none other than to foster awareness of husband and wife in realizing a happy family of sakinah mawaddah warahmah, of course when these rights and obligations are not implemented, it will cause family problems that burden both (husband). and wife) and hampered his success in achieving family expectations. Islam provides rules as well as teachings about procedures for a harmonious family. Likewise, the State binds with responsibility in the form of a marriage law that must be enforced for Indonesian Muslim citizens.